Spatial Analysis For Index Identification Surface Water Pollution - Anang Aris Widodo; Ike Rokhmawati; Anik Vega Vitianingsih; Fitri Marisa; Yunus Susilo (International Applied Science, 2022)
Surface water pollution is an essential problem for policymakers, this is because water is a source of life for the environment. One of the causes of pollution is the company's contribution to waste disposal. The purpose of this research is to identify local pollution points and their pollution status and to map the location of the company to determine the possible contribution of the company to water pollution using a Web-based Geographical Information System (Web-GIS) technology. The data used in this study came from the Environmental and Sanitation Service (DLHK) Sidoarjo Regency. The Pollution Index (IP) method is used for the spatial analysis process based on parameters TSS, DO, BOD, COD, Phosphate, Total Coliform, and Fecal Coliform. The results of spatial analysis using the IP method get an accuracy value of 91% which states that this method is suitable to be recommended for further research with the same data behavior